On a reliable handoff procedure for supporting mobility in wireless sensor networks - Fotouhi, Hossein (2014)
Wireless sensor network (WSN) applications such as patients’ health monitoring in hospitals, location-aware ambient intelligence, industrial monitoring /maintenance or homeland security require the support of mobile nodes or node groups. In many of these applications, the lack of network connectivity is not admissible or should at least be time bounded, i.e. mobile nodes cannot be disconnected from the rest of the WSN for an undefined period of time. In this context, we aim at reliable and real-time mobility support in WSNs, for which appropriate handoff and rerouting decisions are mandatory. This paper1 drafts a mechanism and correspondent heuristics for taking reliable handoff decisions in WSNs. Fuzzy logic is used to incorporate the inherent imprecision and uncertainty of the physical quantities at stake.